Mengenal Tafsir Nusantara: Melacak Mata Rantai Tafsir Dari Indonesia, Malaysia, Thailand, Singapura Hingga Brunei Darussalam - Hasani Ahmad Said (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2017)
Tafsir (exegesis) scholars traced in the Nusantara archipelago, will not be separated from the figure of ‘Abdurrauf al-Fansuri with his Tarjuman alMustafid. Through this work, tafsir had been developed through many media teaching until today. This work also allegedly gave birth to a variety of tafsir model and methodology of qur’anic interpretation in the archipelago. At least two aspects of the interpretation gives birth to the scholars transmission; and to development of the science of interpretation. Firstly, through the activities of teaching; and secondly, through writings. Through these two transmission lines the network of interpretation, until today continues to progress well.